Prevalence of Polycystic Ovarian Syndrome Among High School Students in Benghazi - Amina M., Elsaid; Salma S. Aldaniny; Ahmad M. Elfeituri; Islam Y.Yousef; Lila M. Elfakhery; Yousra S. Aldaniny (Libyan Journal of Medical and Applied Sciences, 2025)
Background: The most common endocrine condition affecting women of reproductive age is polycystic ovarian syndrome, or PCOS. Generally, prevalence of PCOS between 3% and 10%. Metabolic conditions like obesity and insulin resistance (IR) are often associated with PCOS. Many PCOS-afflicted women are overweight or obese and have insulin resistance (IR) with compensatory hyperinsulinemia. It is highly heritable to PCOS. Dietary intakes and physical activity levels that maximise symptom management and disease prevention are not being met by many women with PCOS. Aim of study: To determine the prevalence of PCO among the high school students in Benghazi city. Methodology: Cross-Sectional study, studied 385 Libyan girl aged between 15 – 19 years, Results: The prevalence of PCO among the participant was 5.4%, within some global studies range which (3% - 10%), the study showed that there was a statistical association (p value 0.000) between the obesity, fatty meal intake, family history of PCO and no physical exercise with PCO among the student diagnosed with it. Conclusion: The prevalence of PCOS was found to be similar to the previous global studies. The students with some risk factors like obesity, family history, frequent fatty meal intake and not practice physical exercises more susceptible to PCO syndrome. The modification of lifestyles, diet patterns and physical activity have been proposed.